METAPHORS CORRESPONDENCES OF SOURCE AND TARGET DOMAIN ON THE GOSPEL OF JOHN - Putu Vicka Valleria Angelina; Ni Nyoman Tri Sukarsih (LITERA : Jurnal Bahasa Dan Sastra, 2016)
ABSTRACTThis study purposed at researching the application of conceptual metaphor in teaching of Jesusin John‟s Gospel. The research used qualitative data through text analysis in teachings in John‟sGospel. This research method aimed to explain metaphors and its correspondences betweenSource Domain (SD) and Target Domain (TD). Metaphorical categories were used to classifythe data based on the metaphorical expressions that found in the text of John‟s Gospel. Theanalysis data was explained by ontologism and epistemic. Firstly, the data were collected,selected and classified by three metaphorical categories; there are orientational metaphors,ontological metaphors and structural metaphors. Secondly, to overcome the meaning thatcontained in metaphorical expressions, the data were analyzed to find the correspondence of SDand TD by using ontologism and epistemic.While ontologism is telling about the generalmeaning in reality and epistemic is how the researcher can find any other meaning through thecontext or metaphorical concept.Keywords: metaphorical categories, correspondences, analysis strategies.ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui penggunaan metafora konseptual dalamajaran di Injil Yohanes. Penelitian ini dilaksanakan dengan menggunakan metode kualitatifuntuk menganalisis ajaran yang terdapat pada Inil Yohanes. Metode penelitian yang digunakanadalah metafora dan korespondensi antara ranah sumber (RS) dan ranah target (RT). Datapada ajaran Injil Yohanes yang mengandung metafora diklasifikasi dengan kategori metafora.Kemudian dianalisis secara ontologis dan epistemis. Tahap pertama, data dikumpulkan,diseleksi dan diklasifikasi berdasarkan tiga kategori metafora, yaitu: metafora orientasional,metafora ontologikal dan metafora structural. Tahap kedua, untuk menghasilkan arti yangterkandung dalam data metafora tersebut, data dianalisis dengan mengkorespondensikan RSdan RT secara ontologis dan epistemis. Ontologis adalah proses bagaimana data tersebut dapatdijelaskan secara harfiah dalam arti sebenarnya dan epistemis adalah bagaimana data tersebutdapat diartikan kemudian dihubungkan ke dalam konsep yang lainnya.Kata Kunci: kategori metafora, korespondensi, strategi analisis.